Encapsulated embryogenic callus of clitoria ternatea L. for regeneration and conservation - Mahmad, Noraini; Mat Taha, Rosna; Othman, Rashidi; Elias, Hashimah; Saleh, Azani (IACSIT Press, 2016)
Encapsulated embryogenic callus of Clitoria ternatea L. were successfully created from leaf explants within 3 weeks after germination on Murashige and Skoog (MS) media. The seeds were initially washed with tap water and teepol, then the seeds were sterilised with 99% (v/v) sodium hypochlorite solution for 1 minute and rinsed with distilled water three times. In a laminar flow cabinet, the seeds were dipped in 70% (v/v) ethanol for 1 minute and blotted with steriled tissue. The 3 mm2 leaf explants were encapsulated with 3% alginate (w/v) which were suplemented with various concentrations (0.5-2.5 mg l-1 ) and combinations of NAA, BAP and adenine. The optimum concentration for the formation of encapsulation matrix was 3.0% sodium alginate (NaC6H7O6 ). Encapsulated beads were soaked in 100 mM calcium chloride dehydrate (CaCl2 .2H2O) solution for 30 minutes. No suitable beads were formed with low concentration (1-2%) of sodium alginate. Within 10 minutes soaking in calcium chloride dehydrate, clear and bead formation with no definite shape was observed. While, within 20 minutes in calcium chloride dehydrate, clear beads, solid and round in shape was observed, however, inside the bead was still in liquid condition. In the present study, the rate of germination of synthetic seeds were slightly decreased from 100% to 77% after 60 days of storage at 4°C. Embryogenic tissue from leaf explants of Clitoria ternatea was distinguished by double staining method with bright red of acetocarmine. This technology is an alternative and supplementary method for regeneration, mass propagation and conservation of this medicinal, attractive ornamental and also forage crop for future uses and exploitation